Analysis of the Effect of E-Commerce Usage on MSME Sales: A Case Study of MSMEs in Sleman Regency - Tornado, Febi; Candra, Yudas (Jurnal Ilmiah Manajemen Kesatuan, 2023)
In the Indonesian economy, MSMEs are the largest group of businesses that have shown resilience to various types of economic crisis shocks. E-commerce has recently been favored by both large and small businesspeople. This study aims to determine the analysis of the effect of e-commerce use on MSME sales. This research uses a quantitative approach with correlation and regression analysis tools, to test the level of relationship and influence that occurs between variables. The results of this study indicate that e-commerce on MSME income has a positive and significant effect with a significance value of 0.005 or less than 0.05. This shows that E-Commerce makes a positive contribution, especially in the economic activities of MSMEs by facilitating online trading activities, enabling product marketing in various regions through digital platforms, and facilitating interaction between sellers in Sleman Yogyakarta Regency and buyers from various locations.